2012
DOI: 10.1016/j.metabol.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Insulin clearance is different in men and women

Abstract: Objective Insulin is often infused based upon total body weight (TBW) or fat free mass (FFM)for glucose clamp protocols. We observed greater insulin concentrations in men than women using this approach and examined whether splanchnic insulin extraction accounts for the differences. Materials/Methods Whole body insulin clearance was measured during a pancreatic clamp study (somatostatin to inhibit islet hormone secretion) including 13 adults (6 men) and whole body insulin clearance was measured during a eugly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
9
1
1
Order By: Relevance
“…Although whole-body insulin clearance is greater in women than men, splanchnic insulin extraction is greater in men. Therefore, greater insulin clearance in other peripheral organs accounts for women’s greater whole-body insulin clearance [35]. This finding has led to speculation that women more effectively regulate insulin metabolism in peripheral organs, which is consistent with epidemiological evidence that despite the higher rates of obesity in females, men have higher rates of impaired glucose tolerance and higher incidence of diabetes [36].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although whole-body insulin clearance is greater in women than men, splanchnic insulin extraction is greater in men. Therefore, greater insulin clearance in other peripheral organs accounts for women’s greater whole-body insulin clearance [35]. This finding has led to speculation that women more effectively regulate insulin metabolism in peripheral organs, which is consistent with epidemiological evidence that despite the higher rates of obesity in females, men have higher rates of impaired glucose tolerance and higher incidence of diabetes [36].…”
Section: Discussionmentioning
confidence: 74%
“…Our current results further extend this finding to suggest that the ApoE ε4 gene interacts with sex to moderate treatment response. As noted above, men have a stronger relationship between insulin abnormalities and MCI status [37], and men have less efficient peripheral insulin clearance than women [35]. Therefore it is possible that the ApoE ε4 negative males benefited from the higher dose of intranasal insulin because they were both more sensitive to intranasal insulin and had greater pre-existing insulin abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that (i) the insulin analogue glargine causes a significantly greater decrease in HbA1c in males than females (Osterbrand, Fahlen et al 2007) and that (ii) males respond better to sulfonylureas than females (Donnelly, Doney et al 2006), while (iii) females respond more favorably to rosiglitazone than males (Kim, Cha et al 2005). Our understanding of sex dimorphisms in diabetes is compounded by underlying physiological differences which are numerous and include differences in glucose control and energy homeostasis (Basu, Dalla Man et al 2006), insulin disposal and clearance (Jensen, Nielsen et al 2012), regional fat disposition (Geer and Shen 2009, Macotela, Boucher et al 2009), and sex steroid hormones (Shi and Clegg 2009). For instance, high levels of estrogen confer protection against diabetes development in women (Margolis, Bonds et al 2004, Le May, Chu et al 2006, Shi and Clegg 2009, Tiano and Mauvais-Jarvis 2012), and the decreased estrogen production along with increased longevity in post-menopausal women promotes a greater incidence of T2D in this population compared to males, which is also due to increased longevity in this sex (Gale and Gillespie 2001).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 It is of interest to compare age-related changes in circulating metabolite values in these female offspring with our previously published male data. 7 Serum insulin concentrations are two to five times higher in males than females at postnatal days 110 and 450, potentially reflecting an earlier onset of insulin resistance in males, 22 as well as the documented greater clearance of insulin from the blood in females 23 and lower total body insulin clearance in the elderly than in the young subjects. 24 Insulin sensitivity was demonstrated to be higher in women before menopause than in age-matched men.…”
Section: Discussionmentioning
confidence: 99%